A preliminary study of insect diversity associated with glutinous paddy plant at Telok Chengai, Alor Setar, Kedah, Malaysia - Nurul Farisa Reward,; Muhammad Muzzammil Mohd Nizar,; Zulidzham Mohd Sani,; Mohd. Fahimee Jaapar, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2022)
A preliminary study of insect diversity associated with glutinous paddy plant was conducted from July to September 2019 in Telok Chengai, Alor Setar, Kedah, Malaysia. Six samplings of insects were carried out during the growing phase at six plot paddy fields with an area of 5.53ha starting from the active tillering stage until the flowering stage. Sweep net and insects scoring sampling methods were used for insect collections, and identification process at the laboratory. The data were determined by using a descriptive statistic, diversity index, and statistical test for mean comparisons. A total of 791 individuals comprising 44 species representing 36 families and seven orders of insects were recorded. From the total of the insects collected, the insects can be categorized into ecological guilds. The pest was dominant with 459 individuals (58.03%) followed by the predators (261 individuals, 33.0%), the parasitoids (12 individuals, 1.5%), and other groups of insects (59 individuals, 7.46%). For index diversity analysis of the total growing phase, the maximum tillering stage had the highest insect’s diversity with Shannon-Wiener diversity index (H’) of 2.40 and Margalef Richness index (R) of 5.82, whereas the flowering stage had the lowest H’ of 1.68 and R of 2.52. However, there was no significant differences (P>0.05) of insect abundance between the stages of growing paddy fields. Results for this preliminary study indicated that the population of pest in the glutinous paddy field population was dominant compared to the beneficial insects and other insect communities during various phases of glutinous paddy development that may cause a loss in yield. Therefore, this database can be used for future insect pest management of the glutinous paddy ecosystem in Malaysia.